What America's Users Spend on Illegal Drugs, 2000-2010 - Kilmer, Beau (RAND Corporation, 2014)
RAND researchers generated national estimates of consumption of four illicit drugs from 2000 to 2010: cocaine, heroin, marijuana, and methamphetamine. Throughout the decade, U.S. drug users spent on the order of $100 billion annually on these drugs, although the spending distribution and use patterns changed. For all of the drugs, total consumption and expenditures are driven by the minority of users who consume on 21 or more days each month.